Building strong banks : through surveillance and resolution - Marston, David; Enoch, Charles; Taylor, Michael (Washington, D.C. : International Monetary Fund, 2002)
This book contains a collection of essays --- drawn from practical experience --- on a wide range of issues germane to bolstering the banking and financial sector, including developing adequate standards for loan classification and povisioning and promoting deep and liquid money markets.
Includes bibliographical references.
gau 17/06/14
Loans
Keywords: Banks and banking - state supervision; Monetary policy; Financial institutions- state supervision; Financial institutions - government policy; Banks and banking - government policy; International Monetary Fund